2008
DOI: 10.1007/s10725-008-9308-1
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced oxidative damage and antioxidative defense mechanisms in Vigna mungo L.

Abstract: Cadmium (Cd)-induced oxidative stress and antioxidant defense mechanisms were analyzed in roots and leaves of Vigna mungo L. Seeds were germinated in perlite-vermiculite and irrigated with Hoagland nutrient solution. At day 6, seedlings were exposed to 40 lM Cd under semi-hydroponic conditions for a period of 12 days. Growth anomalies and abnormal chromatin condensation were observed in Cd-treated plants, in comparison with control ones. Cd accumulation was observed in roots of treated plants. The analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 39 publications
6
21
0
1
Order By: Relevance
“…Accumulation of α-tocopherol, ascorbic acid and carotenoids levels in cadmium treated pea seedlings as being compared with control indicate their protective role against oxidative damage. Similar to the present results, other investigations have shown increased in α-tocopherol and ascorbic acids levels for different plant species exposed to cadmium (Liu et al, 2007;Molina et al, 2008;Zengin and Munzuroglu, 2005). Calcium chloride application either alone or in combination with cadmium acetate increased carotenoids content as compared with those of control plants.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Accumulation of α-tocopherol, ascorbic acid and carotenoids levels in cadmium treated pea seedlings as being compared with control indicate their protective role against oxidative damage. Similar to the present results, other investigations have shown increased in α-tocopherol and ascorbic acids levels for different plant species exposed to cadmium (Liu et al, 2007;Molina et al, 2008;Zengin and Munzuroglu, 2005). Calcium chloride application either alone or in combination with cadmium acetate increased carotenoids content as compared with those of control plants.…”
Section: Resultssupporting
confidence: 92%
“…Excessive Cd induces complex changes in plants at genetical, biochemical and physiological levels, leading to phytotoxicity. The most obvious symptoms are (1) depression of plant growth and even resulting in plant death by disturbing the uptake of nutrients (Hassan et al, 2005); (2) destruction of photosynthesis via degradation of chlorophyll (Hassan et al, 2005;Shamsi et al, 2008a) and inactivation of enzymes involved in CO 2 fixation (De Filippis and Ziegler, 1993) or the aggregation of pigment protein complexes of the photosystems (Horvath et al, 1996); (3) interaction with the water balance of the plant and inhibiting stomatal opening (Barcelo and Poschenrieder, 1990); (4) alteration of proline and polyamine contents (Sharma and Dietz, 2006); and (5) accelerating lipid peroxidation and affecting cell membrane fluidity and permeability due to an alteration in the composition of membrane lipids (Molina et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We observed this behavior, where GSH increase responsed to Cd toxicity [11,12] ; also this behavior was observed in previous work in Vigna mungo L. under Cd exposure [13] .…”
Section: Discussionsupporting
confidence: 89%
“…After exposure to Cd, it is accumulated in different vegetal parts, preferentially in roots [13,14] , and only a small portion is transported to the aerial organs.…”
Section: Cyclingmentioning
confidence: 99%
“…Both lipid peroxidation and excessive copper accumulation in root tissue were suggestive of the fact that oxidative stress and lipid peroxidation were due to the release of free radicals in the root tissues of bean plants (Yurekli and Porgali 2006). In contrast, the level of lipid peroxidation quantified as MDA content though decreased in roots but increased in leaves of Vigna mungo (L.) grown in perlite-vermiculite using Hoagland nutrient solution treated with 40 mM cadmium (Molina et al 2008). In line with these findings, other researchers have also reported that copper is capable of forming toxic oxygen and starting the process of lipid peroxidation quite effectively (Girotti 1985;Luna et al 1994;Weckx and Clijsters 1996).…”
Section: Lipid Peroxidationmentioning
confidence: 80%